(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: - Parte Prima. Un virus tra Stato e Chiesa cattolica - 1. Brevi considerazioni introduttive - 2. Misure di contenimento della diffusione della malattia da Covid-19 in Italia: il quadro normativo - 3. Le (cogenti) misure restrittive sull’esercizio del culto - 4. Limiti alla libertà della missione pastorale ed alla libera organizzazione del pubblico esercizio del culto, del magistero e del ministero spirituale della Chiesa cattolica - 5. Un virus nei principi di bilateralità e degli ordini distinti - Parte Seconda. Limiti alla libertà religiosa ed all’esercizio del culto nell’emergenza sanitaria - 6. Strumenti normativi per fronteggiare la crisi sanitaria e questioni di legittimità: brevi cenni - 7. Libertà religiosa e diritto alla salute: bilanciamento tra diritti fondamentali - 8. L’anima dei cives-fideles ai tempi del coronavirus. Souls quarantine of the cives-fideles. The exercise of worship in the health emergency from Covid-19 in Italy ABSTRACT: The Italian government has issued regulatory provisions during the lockdown due to health emergency from Covid-19, in order to prevent the spread of epidemiological outbreaks. These new rules have not fulfilled the agreements made with Catholic Church, specificly article 2 of Agreement 1984, especially about the freedom of management and organization of pastoral activities, and they have imposed serious restrictions on the right to religious freedom too. In particular, in order to avoid gatherings, the emergency rules have suppressed the religious ceremonies, as well as masses and last rites. Only recently the right to exercise worship was partially allowed and on May 7th, 2020, a Protocol was signed with Italian Episcopal Conference for the gradual reopening of the celebrations coram populo. The issue concerns the balance between the right to health and the rights of freedom. The question is whether this balance of rights was correctly applied.